Simulation and Analysis of Distributed Reaction Systems - Brodo, Linda; Bruni, Roberto; Falaschi, Moreno; Petre, Ion (Institute of Electrical and Electronics Engineers (IEEE), 2025)
Reaction systems (RSs) are a computational framework inspired by the interplay between biochemical interactions. Similarly to regulatory networks, reaction products can dynamically activate or inhibit other reactions. This provides a framework for discrete-time, interactive computation, where each state is determined by those reactions enabled in the immediately preceding state and by additional environmental interventions, if any. Since their introduction, RSs have been extended to study many aspects of complex systems: multi-agent collaborations, cause-effect relationships, model checking, and many others. The gap in the literature addressed in this paper is the lack of software tools for simulating and analysing distributed reaction systems (DRSs). We introduce a process algebraic approach to describing, simulating, and analysing DRSs. This allows designing complex models by re-using modular components in a well-structured and compositional way, and analysing them with the BioReSolve modelling software. We demonstrate our approach by experimenting with distributed Lotka-Volterra models, where multiple agents evolve according to their own periodic dynamics, but can also synchronise their cycles through diverse communication topologies.